Activity-Dependent Plasticity of Astroglial Potassium and Glutamate Clearance - Giselle Cheung; Jérémie Sibille; Jonathan Zapata; Nathalie Rouach (Neural Plasticity)
Recent evidence has shown that astrocytes play essential roles in synaptic transmission and plasticity. Nevertheless, how neuronal activity alters astroglial functional properties and whether such properties also display specific forms of plasticity still remain elusive. Here, we review research findings supporting this aspect of astrocytes, focusing on their roles in the clearance of extracellular potassium and glutamate, two neuroactive substances promptly released during excitatory synaptic transmission. Their subsequent removal, which is primarily carried out by glial potassium channels and glutamate transporters, is essential for proper functioning of the brain. Similar to neurons, different forms of short- and long-term plasticity in astroglial uptake have been reported. In addition, we also present novel findings showing robust potentiation of astrocytic inward currents in response to repetitive stimulations at mild frequencies, as low as 0.75 Hz, in acute hippocampal slices. Interestingly, neurotransmission was hardly affected at this frequency range, suggesting that astrocytes may be more sensitive to low frequency stimulation and may exhibit stronger plasticity than neurons to prevent hyperexcitability. Taken together, these important findings strongly indicate that astrocytes display both short- and long-term plasticity in their clearance of excess neuroactive substances from the extracellular space, thereby regulating neuronal activity and brain homeostasis.